EIB Working Paper 2023/05 - European Investment Bank (European Investment Bank, 2024)
The COVID-19 shock had a strong negative effect on aggregate economic performance, with the average firm taking a hit on sales revenues and financial performance. However, the effects varied from firm to firm. Were already-struggling firms hit hardest, threatening their very survival? Or did the COVID-19 shock disproportionately deter tomorrow’s superstars at the upper end of the distribution, thus sacrificing future growth potential? This paper investigates where the COVID-19 shock hit the firm growth distribution, using graphical techniques and quantile regressions to analyse the full distribution of firm growth rates. We investigate how the COVID-19 shock relates to growth outcomes for four dependent variables: growth of sales, value added, employment, and labour productivity. Our results confirm that COVID-19 policy support reached its intended recipients.